Pengaruh Tarif Pajak, Teknologi Dan Informasi Perpajakan, Ketepatan Pengalokasian Pajak Terhadap Persepsi Wajib Pajak Mengenai Penggelapan Pajak (Tax Evasion) Pada Kpp Pratama Jakarta Pademangan Tahun 2022 - Dewi, Julianti; Biettant, Rubiatto (Jurnal Ilmu Administrasi Publik, 2024)
This study discusses Tax Rates, Tax Technology and Information, and the Accuracy of Tax Allocation on Taxpayers' Perceptions Regarding Tax Evasion. The purpose of this study is to analyse the influence of Tax Rates, Tax Technology and Information, and the Accuracy of Tax Allocation. The method used in this research is a quantitative approach. The population in this study consists of individual and corporate taxpayers registered at Primary Tax Service Office (KPP Pratama) of Jakarta Pademangan. The total population of taxpayers in 2022 was 97,958, and the sample size in this study was 398 respondents. The data analysis methods used include Instrument Testing, Validation Testing, Reliability Testing, Descriptive Statistics Testing, followed by classical assumption tests and hypothesis testing with T-tests, F-tests, Correlation Coefficient Tests, and Determination Coefficient Tests. Based on the research results, it is known that the tax rate has a significant effect with a T-value of 7.361, tax technology and information have a significant effect with a T-value of 8.198, and the accuracy of tax allocation has a significant effect with a t-value of 4.163. The simultaneous test results (F-test) show an F-value of 28.247 with a significance of (0.000) < 0.05, indicating that the hypothesis, namely Tax Rates, Tax Technology and Information, and the Accuracy of Tax Allocation on Taxpayers' Perceptions Regarding Tax Evasion, can be accepted. The combined influence is 57.1%.